2016
DOI: 10.1016/j.ijcard.2016.08.267
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of significant coronary artery disease in atrial fibrillation: Are cardiac troponins a useful measure

Abstract: Background: Cardiac Troponin I (cTnI) is frequently measured in patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
19
1
1
Order By: Relevance
“…Other previous studies addressing the significance of troponin elevations in AF patients are to our knowledge all retrospective, use the older 4 th generation troponin assays and come to different conclusions [2,3,[26][27][28]. Some report an increased risk of MI and cardiac death during follow-up [2,3,27] while others fail to show that elevated troponin predicts significant CAD on angiography or 10 adverse cardiac events during follow-up [26,28]. Some of the reasons for this diversity may be different study populations and the use of different troponin assays with different cut offs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies addressing the significance of troponin elevations in AF patients are to our knowledge all retrospective, use the older 4 th generation troponin assays and come to different conclusions [2,3,[26][27][28]. Some report an increased risk of MI and cardiac death during follow-up [2,3,27] while others fail to show that elevated troponin predicts significant CAD on angiography or 10 adverse cardiac events during follow-up [26,28]. Some of the reasons for this diversity may be different study populations and the use of different troponin assays with different cut offs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Other previous studies addressing the significance of troponin elevations in AF patients are to our knowledge all retrospective, use the older 4 th generation troponin assays and come to different conclusions [2,3,[26][27][28]. Some report an increased risk of MI and cardiac death during follow-up [2,3,27] while others fail to show that elevated troponin predicts significant CAD on angiography or adverse cardiac events during follow-up [26,28]. Some of the reasons for this diversity may be different study populations and the use of different troponin assays with different cut offs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Alghamy et al [50] investigated the predictive value of elevated cTnI for severe coronary artery disease (sCAD) in patients presenting with atrial fibrillation (afib). They conducted a retrospective case-control study and found that troponin elevation above the 99 th percentile cut-off did not predict sCAD; however, elevatedcTnI was a strong indicator of sCAD especially if it exceeded 2.1 micrograms per liter [50]. Tachyarrhythmias should be considered a possible etiology of elevated troponins in patients presenting with elevated cardiac troponins who do not have ischemic risks factors or a clinical picture consistent with AMI.…”
Section: Arrhythmiasmentioning
confidence: 99%
“…Bakshi et al [12] noted that tachycardia was the cause of elevated troponins in 28% of patients without coronary artery disease as determined by lack of obstructive disease on left heart catheterization [12,49]. Alghamy et al [50] investigated the predictive value of elevated cTnI for severe coronary artery disease (sCAD) in patients presenting with atrial fibrillation (afib). They conducted a retrospective case-control study and found that troponin elevation above the 99 th percentile cut-off did not predict sCAD; however, elevatedcTnI was a strong indicator of sCAD especially if it exceeded 2.1 micrograms per liter [50].…”
Section: Arrhythmiasmentioning
confidence: 99%